Comparison of Buccal Corridor Width in Post Treatment Patients Treated with Non Extraction Vs Extraction Therapy in Mithilanchal Population - Sarkar, Darshana; Mishra, Praveen; Kumar, Santosh (Orthodontic Journal of Nepal, 2022)
Introduction: A wide variety of opinion exists on the effect of extraction on the buccal corridor width which has a direct impact on smile esthetics. Till date no study regarding this has been done in Mithilanchal population. Aims and objectives: To compare the post-treatment buccal corridor width and posterior corridor width of patients treated with or without four first premolars extraction in Mithilanchal population. Materials and Methods: This was a cross-sectional study conducted at department of orthodontics and dentofacial orthopedics in Mithila Minority Dental College and Hospital, Darbhanga, Bihar. Post treatment posed smile photographs of 24 extraction patients and 24 non-extraction patients were compared using standardization and cropping in adobe Photoshop version 7.0. Statistical analysis was done with SPSS software (IBM Corp 2013; Version 22.0; Armonk, NY) and independent t-test to compare buccal corridor width and posterior corridor width between two groups. Results: The age group of subjects varied from 1 3 to 26 years. The mean age of group 1 (extraction) and group 2 (non-extraction) patients were 1 7.75 ± 4.48 years and 20.21 ± 4.03 years respectively. The mean width of buccal corridor in extraction patients were 35.33 ± 1 .52 % and for non-extraction group was found to be 35.38 ± 1 .54 %. (non-significant, p = 0.903). The posterior corridor mean width was 20.46 % in group 1 patients and 19.83% in group 2 patients (non-significant, p = 0.274). Conclusion: No significant difference in the buccal corridor and posterior corridor widths was found after orthodontic treatment with and without extraction of the first four premolars.